Voluntary environmental regulations and their impact on marginal abatement costs: empirical results from the national ecological demonstration park - Gao, Jian; Wu, Kaibin; Hong, Fubin; Xu, Huiming; Qiu, Zejing; Sun, Yue (Frontiers in Environmental Science, 2025)
During China’s industrialization, its development zones encountered issues of environmental pollution and resource depletion while fostering economic growth. For this reason, the Chinese government encouraged the establishment of national eco-industrial demonstration parks (NEDP). Based on data from 211 Chinese cities with National Development Zones from 2003 to 2020, this article uses the construction of NEDP as the research entry point to study the role of self-regulated environmental policies on the marginal abatement cost (MAC) of CO2. The multi-period DID method is used for the analysis. We find that the NEDP policy plays a key role in significantly reducing the MAC of CO2 in urban areas. The NEDP policy affects cities’ MAC of CO2 through green innovation and carbon intensity effects. Although the latter offsets part of the reduction, the former dominates, resulting in a significant overall decrease in marginal abatement costs. However, the policy’s effects exhibit some delay. The impact of the NEDP policy varies across cities, primarily influenced by the policy’s intensity and the timing of the parks’ establishment. Multiple demonstration parks and parks established at an early stage see greater reductions in abatement costs. On the other hand, single parks or those developed at later stages do not lead to a significant reduction in abatement costs and may, in fact, cause an increase in costs due to the carbon intensity effect. The policy implications suggest that the government should accelerate park transformation and promote multiple demonstration parks to maximize emission reduction benefits. Encouraging resource sharing between parks and advancing green technology innovation can strengthen the validity of voluntary environmental regulation. Additionally, the government should refine park construction strategies, adopting differentiated policies, especially for late-stage parks, and support green technology innovation to avoid rising emission reduction costs due to technological constraints.